сделай лучшим ❤️
для меня это важно ❤️
1) (x-2)(x+3)+(x+2)(x-3) = + 3x - 2x - 6 + - 3x + 2x - 6 = - 2x - 6 + + 2x - 6 = - 6 + - 6 = 2 - 12
2) (a+1)(a + 2) + (a + 3)(a + 4) = + 2a +a +2 + + 4a +3a + 12 = 2 + 10a + 14
3) (а – 1)(а+ 2) + (а+1)(а – 2) = - 2 + - 2 = 2 - 4
4) (х – 1)(х – 2) + (х – 3)(х – 4) = - 2x - x + 2 + - 4x - 3x + 12 = 2 - 10x + 2 +12 = 2 - 10x + 14
сделай лучшим ❤️
для меня это важно ❤️
1) (x-2)(x+3)+(x+2)(x-3) =
+ 3x - 2x - 6 +
- 3x + 2x - 6 =
- 2x - 6 +
+ 2x - 6 =
- 6 +
- 6 = 2
- 12
2) (a+1)(a + 2) + (a + 3)(a + 4) =
+ 2a +a +2 +
+ 4a +3a + 12 = 2
+ 10a + 14
3) (а – 1)(а+ 2) + (а+1)(а – 2) =
- 2 +
- 2 = 2
- 4
4) (х – 1)(х – 2) + (х – 3)(х – 4) =
- 2x - x + 2 +
- 4x - 3x + 12 = 2
- 10x + 2 +12 = 2
- 10x + 14